Novel TaqMan® real-time PCR targeting invJ gene for 8-h detection of Salmonella from food matrices - Isaac, Ann Mary; Kolla, Harish Babu; Pallavi, K. P.; Bandyadka, Sharat; Mhatre, Chinmayi Nandkishor; Urs, Radhika Madan; Kingston, J. Joseph (Frontiers in Microbiology, 2025)
Salmonella, a well-known food-borne zoonotic pathogen, is the causative agent of Salmonellosis affecting public health in both developed and developing countries. Traditional Salmonella detection methods are time-consuming, involving multiple steps like pre-enrichment, selective plating, and biochemical confirmation. In this study, a faster and sensitive TaqMan® real-time PCR assay was developed with a 6 h enrichment paradigm for the direct detection of Salmonella from food matrices using a novel target gene, invJ, which is part of the Salmonella Type 3 Secretion System (T3SS). The assay was found to be highly specific and had a limit of detection of 102 CFU/mL Salmonella in pure culture. With a 6-h enrichment step, the assay was able to detect even low bacterial inoculum like 100 CFU/mL of S. Typhimurium in both artificially contaminated raw foods (raw egg and frozen chicken) and cooked Indian food matrices (ready-to-eat chicken biriyani and chicken pulao). The assay demonstrated 100% relative sensitivity, specificity, and accuracy across 52 natural (raw and processed) food samples. In summary, the real-time Salmonella detection method developed is faster, specific, sensitive and a potential tool for regular Salmonella monitoring in diverse food matrices within 8 h.